Estudo da toxicidade de garrafada de uso popular - Indras, Denise Michelle (2017)
The popular use of medicinal plants are common practices and among them is a bottle, a multiple plant base product, which promises to cure various diseases. Many animal studies show in hepatic, renal enzymes and our hematological parameters after administration of plant extracts. The objective of this study was to verify a correlation between the use of multiple medicinal plants with hepatic, renal and hematological found in a patient that made use of bottle, composed of echinacea, graviola, ipé purple, sucupira and cat's claw. The bottle has 4.32 mg.mL-1 of alcohol. Pharmacological and UV/Scan tests were performed, showing some classes of secondary metabolites in plant and bottle species. A bioassay was performed with Artemia salina, and a bottle had mortality up to a concentration of 0.1 mg.mL-1. Cytotoxic effects on erythrocytes revealed hemolytic activity for echinacea, graviola, purple ipe and sucupira. The Escherichia coli test showed sensitivity to graviola, purple ipe, sucupira and cat's claw. In vivo experiment using mice. Two treatments were performed, single dose and 30 days, administering water, alcohol and bottle by gavage. Biochemical, coagulation, hematological and histopathological parameters were evaluated. In the single dose treatment were alterations of uric acid, cholesterol, creatinine, alkaline phosphatase, iron and glucose (p<0.05). Already in the treatment of 30 days were alterations of uric acid, total and indirect bilirubins, creatinine, alkaline phosphatase, glucose, triglycerides, red blood cells and leukocytes (p<0.05), beyond hepatic sinusoidal dilatation. The data showed that the alcohol present in the bottle can alter biochemical, hematological parameters and cause liver damage in rats. The bottle, although not showing alterations in important biochemical and hematological parameters, but had more pronounced hepatic histopathological alterations.